How does climate exacerbate root causes of conflict in Zimbabwe? An impact pathway analysis - Madurga Lopez, Ignacio M.; Dutta Gupta, Tanaya; Läderach, Peter R.D.; Pacillo, Grazia (2021)
This factsheet gives answers on how climate exacerbates root causes of conflict in Zimbabwe, using an impact pathway analysis. Two main impact pathways are identified: 1) Food insecurity and competition over access and use of natural resources; 2) Water scarcity and conflict in Bulawayo and Matabeleland North.